2020
DOI: 10.1016/j.heliyon.2020.e04649
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between demographic factors and upper urinary tract stone composition in the Thai population

Abstract: Objective To identify the correlation between demographic factors and upper urinary tract stone composition in the Thai population. Method A retrospective observational study of first-time upper urinary tract stone former patients aged over 18 years who underwent stone surgery was performed in a tertiary referral university hospital from January 2013 to May 2018. Collected data included demographic information and stone composition information, which were analysed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The beginning of urolithiasis prevalence studies in Thailand dates to 1961, with a reported prevalence of 17.7/100,000, which increased to 183.8/100,000 in the year 2005;[ 7 - 9 ] this had a significant impact on health systems due to the cost of diagnosis and treatment, as well as the loss of working hours due to the disease. [ 10 ] This led to the development of community treatment programs, resulting in a decreased prevalence of 90.75/100,000 people in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The beginning of urolithiasis prevalence studies in Thailand dates to 1961, with a reported prevalence of 17.7/100,000, which increased to 183.8/100,000 in the year 2005;[ 7 - 9 ] this had a significant impact on health systems due to the cost of diagnosis and treatment, as well as the loss of working hours due to the disease. [ 10 ] This led to the development of community treatment programs, resulting in a decreased prevalence of 90.75/100,000 people in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…1 Bladder stones are usually symptomatic; but in a few cases, they can also be asymptomatic. 2,3 Open cystolithotomy and endoscopic modalities are the available methods for the removal of bladder stones. 4 Open cystolithotomy is associated with more postoperative pain, prolonged hospital stays and wound scar as compared to endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Urolithiasis is a frequently occurring urological disease characterized by the presence of a stone anywhere along the urinary tract, with a high recurrence rate [1]. Arunkajohnsak et al found that the major components of the stone consist of calcium oxalate (60%), calcium phosphate (26%), uric acid (8.3%), magnesium ammonium phosphate (4.0%), cystine (1.0%), and ammonium hydrogen urate (0.6%) [2]. The pathogenesis is a complex biochemical process that is not completely understood.…”
Section: Introductionmentioning
confidence: 99%